Amplitude-dependent internal friction in AZ31 alloy sheets submitted to accumulative roll bonding - Trojanová, Z.; Drozd, Z.; Lukáč, P.; Minárik, P.; Džugan, J.; Halmešová, K. (Физика низких температур, 2018)
Fine grained magnesium alloy AZ31 sheets were submitted to the accumulative roll bonding (ARB). After ARB, the microstructure of samples was refined, and the sheets exhibited pronounced texture. The amplitudedependent internal friction (ADIF) was measured at room temperature. Microstructure changes as the increased dislocation density, grain size refinement, twins, and texture influenced the ADIF. A significant anisotropy of the properties was observed. Experimental results are discussed on the base of physical mechanisms responsible for internal friction.